Ecofriendly spectrophotometric estimation of tinidazole in tablets using lignocaine hydrochloride as a hydrotropic solubilizing agent - Maheshwari, RK; Rajput, MS; Sinha, S (Asian Journal of Pharmaceutics (AJP), 2014)
Anovel, safe and sensitive method of spectrophotometric estimation in the ultraviolet region has been developed using1M lignocaine hydrochloride (an economic drug) as a hydrotropic solubilizing agentfor the quantitative determinationof tinidazole, a sparingly water-soluble antiprotozoal drug in tablet dosage form. Beer’s law was obeyed in the concentration range of 5-25 mg/ml. Lignocaine hydrochloride does not interfere above 280 nm.There was more than a six-fold enhancement in aqueous solubility of tinidazole in 1M lignocaine hydrochloride solution as compared with the solubility in distilled water. Commonly used tablet excipients and lignocaine hydrochloride did not interfere in spectrophotometric estimation. Results of the analysis were validated statistically and by recovery studies. The results of analysis obtained by the proposed method were comparable with the results of analysis obtained by the Indian Pharmacopoeial method.